Inner magnetosphere coupling: Recent advances. Issue 1 (9th January 2017) - Usanova, M. E.; Shprits, Y. Y.
Abstract: The dynamics of the inner magnetosphere is strongly governed by the interactions between different plasma populations that are coupled through large‐scale electric and magnetic fields, currents, and wave‐particle interactions. Inner magnetospheric plasma undergoes self‐consistent interactions with global electric and magnetic fields. Waves excited in the inner magnetosphere from unstable particle distributions can provide energy exchange between different particle populations in the inner magnetosphere and affect the ring current and radiation belt dynamics. The ionosphere serves as an energy sink and feeds the magnetosphere back through the cold plasma outflow. The precipitating inner magnetospheric particles influence the ionosphere and upper atmospheric chemistry and affect climate. Satellite measurements and theoretical studies have advanced our understanding of the dynamics of various plasma populations in the inner magnetosphere. However, our knowledge of the coupling processes among the plasmasphere, ring current, radiation belts, global magnetic and electric fields, and plasma waves generated within these systems is still incomplete. This special issue incorporates extended papers presented at the Inner Magnetosphere Coupling III conference held 23–27 March 2015 in Los Angeles, California, USA, and includes modeling and observational contributions addressing interactions within different plasma populations in the inner magnetosphere (plasmasphere, ring current, and radiation belts), coupling between fields and plasma populations, as well as effects of the inner magnetosphere on the ionosphere and atmosphere. Key Points: The dynamics of the inner magnetosphere is strongly governed by the interactions between different plasma populations Our understanding of the coupling processes in the magnetosphere is still incomplete This special issue contains a collection of papers advancing our knowledge of the processes affecting the inner magnetosphere